Splanchnic Vein Thrombosis - Valla, Dominique (Seminars in Thrombosis and Hemostasis, 2015)
Splanchnic vein thrombosis includes thrombosis of the hepatic venous system (Budd–Chiari syndrome) and thrombosis of the portal venous system. Both conditions share uncommon prothrombotic disorders as causal factors, among which myeloproliferative neoplasms rank first. Budd–Chiari syndrome presents with acute or chronic, asymptomatic or severe liver disease. Diagnosis depends on noninvasive imaging of the obstructed hepatic venous outflow tract. A spontaneously fatal course can be prevented by a stepwise approach: (1) anticoagulation therapy, specific therapy for underlying disease, and medical or endoscopic management of liver-related complications, (2) angioplasty/stenting in a second step, and (3) eventually the insertion of transjugular intrahepatic stent shunt or liver transplantation. Recent portal vein thrombosis mostly jeopardizes the gut. Early anticoagulation prevents thrombus extension but is incompletely successful in achieving recanalization. Chronic portal vein thrombosis is complicated by bleeding related to portal hypertension, which can be prevented by usual pharmacological and endoscopic means. The prevention of recurrent thrombosis is achieved by anticoagulation therapy the impact of which on the risk of bleeding remains unclear. Portal vein thrombosis in patients with cirrhosis is likely neither a direct consequence of nor a direct cause for liver disease progression. Therefore, the indications and effects of anticoagulation therapy for portal vein thrombosis in patients with cirrhosis remain uncertain.
Keywords: hepatic vein thrombosis; Budd–Chiari syndrome; portal vein thrombosis; cavernoma; TIPS